(untitled) (BioLaw Journal - Rivista di BioDiritto, 2019)
Despite the lack of significant competences of the Union in this respect, several dynamics facilitate the encounter between Union law and biolaw. Amongst these, the protection of fundamental rights has become more prominent following the elaboration of the Charter of fundamental rights of the European Union and the subsequent recognition of its Treaty-like status. The occasions for the Court of Justice to deal with biolaw issues have increased. From a substantive point of view, this case law shows that the Court can actively contribute to the development of a European biolaw.